Severe abnormal Heart Rate Turbulence Onset is associated with deterioration of liver cirrhosis. - Christian Jansen; Baravan Al-Kassou; Jennifer Lehmann; Alessandra Pohlmann; Johannes Chang; Michael Praktiknjo; Georg Nickenig; Christian P Strassburg; Jan W Schrickel; René Andrié; Markus Linhart; Jonel Trebicka (PLoS ONE, 2018)
In patients with liver cirrhosis, cardiac dysfunction is frequent and is associated with increased morbidity and mortality. Cardiac dysfunction in cirrhosis seems to be linked to autonomic dysfunction. This study investigates the role of autonomic dysfunction assessed by Heart Rate Turbulence (HRT) analyses in patients with liver cirrhosis.Inclusion criteria was (1) diagnosis of cirrhosis by clinical, imaging or biopsy and (2) evaluation by standard 12-lead-ECG and 24h holter monitoring and (3) at least 3 premature ventricular contractions. The exclusion criterion was presence of cardiac diseases, independent of liver cirrhosis. Biochemical parameters were analysed using standard methods. HRT was assessed using Turbulence onset (TO) and slope (TS). The endpoint was deterioration of liver cirrhosis defined as increased MELD and readmission for complications of liver cirrhosis.Out of 122 cirrhotic patients, 82 patients (63% male) with median Child score of 6 (range 5-12) and median MELD score of 10 (range 6-32) were included. Increasing Child score, INR and decreasing albumin were correlated with TO. In addition, decompensated patients with ascites showed more abnormal TO and TS. During the observation period, patients with more abnormal TO showed significantly higher rate of rising MELD Score at 6 months (p = 0.03). Nevertheless, at least in our collective HRT-parameters were not independent predictors of deterioration of cirrhosis.Parameters of HRT are closely associated with deterioration of cirrhosis and might be helpful in its prediction.